2017
DOI: 10.1007/s10911-017-9381-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitrosamine (NNK) in Breast Cancer Carcinogenesis

Abstract: Smoking cigarettes is one of the most concerning issues that leads to tobacco-related cancers and can even result in death. Therefore, these issues should be addressed with a great sense of urgency with low-cost and simple approaches. Over the past several years, the scientific community has attempted to find solutions to overcome this issue. Thus, a large number of excellent studies have been reported in this field, and summarizing these results and providing important roadmaps for future studies is currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 127 publications
0
19
0
Order By: Relevance
“…Garlic has anticancer effects through inhibiting the production and bioactivity of nitrosamines (Atanasova‐Goranova, Dimova, & Pevicharova, ). Nitrosamines play important roles in causing and increasing the risk of cancer (Gankhuyag, Lee, & Cho, ). Belloir et al, indicated that SAC and allyl mercaptan (C 3 H 6 S) significantly inhibited dimethyl nitrosamine genotoxicity (Belloir et al, ) by affecting the metabolizing enzyme, cytochrome P450 2E1 (CYP2E1; Yamazaki et al, ).…”
Section: A Sativummentioning
confidence: 99%
“…Garlic has anticancer effects through inhibiting the production and bioactivity of nitrosamines (Atanasova‐Goranova, Dimova, & Pevicharova, ). Nitrosamines play important roles in causing and increasing the risk of cancer (Gankhuyag, Lee, & Cho, ). Belloir et al, indicated that SAC and allyl mercaptan (C 3 H 6 S) significantly inhibited dimethyl nitrosamine genotoxicity (Belloir et al, ) by affecting the metabolizing enzyme, cytochrome P450 2E1 (CYP2E1; Yamazaki et al, ).…”
Section: A Sativummentioning
confidence: 99%
“…Bychkov et al and Lyukmanova et al confirmed that the expression of functional α7-nAChRs on the cancer cells membrane by confocal microscopy [8,11], suggesting that the homomeric channels that had been composed of α7 subunits are a valuable therapeutic target for cancers. The main argument was that nicotine activated α7 nAChRs can cause Ca 2+ influx into cancer cells and trigger membrane depolarization, which activates voltage-gated Ca 2+ channels and subsequently activates the MAPK pathway, which may result in inhibition of apoptosis [41,42]. Except for α7 nAChRs, the homopentameric structure of α9 nAChRs has been confirmed to play a major role in breast cancer and other cancer cells [8,11,19,34].…”
Section: Discussionmentioning
confidence: 99%
“…The use of tobacco is related to the development of numerous pathologies, including lung cancer that represents the leading cause of cancer death worldwide, including both the male and the female population 30 . Regarding breast cancer, studies have demonstrated that not only active smoking, but also passive smoking, can predispose the individual to the risk of developing the disease 8,31 .…”
Section: Tobacco Consumptionmentioning
confidence: 99%
“…Among the thousands of chemical products found in tobacco, 69 different compounds are classified as carcinogenic, specifically, the 4-(methylnitrosamino) -1-(3-pyridyl) -1-butanone (NNK) (Nicotine-derived nitrosamine ketone), considered the most aggressive nitrosamine among the ones present in tobacco 31 . NNK is found in cigars, cigarettes, electronic cigarettes, tobacco and in the smoke from these products, causing nitrosamines to affect not only the consumer, but also non-smokers or passive smokers exposed to environmental tobacco pollution 31 . On the other hand, environmental exposure to tobacco was criticized, and a meta-analysis published by Lee and Hamling assessed 47 studies.…”
Section: Tobacco Consumptionmentioning
confidence: 99%